2012
DOI: 10.1103/physreve.85.016322
|View full text |Cite
|
Sign up to set email alerts
|

Droplet formation in microfluidic T-junction generators operating in the transitional regime. I. Experimental observations

Abstract: This is the first part of a two-part study on the generation of droplets at a microfluidic T-junction operating in the transition regime where confinement of the droplet creates a large squeezing pressure that influences droplet formation. In this regime, the operation of the T-junction depends on the geometry of the intersection (height-to-width ratio, inlet width ratio), capillary number, flow ratio, and viscosity ratio of the two phases. Here in paper I we presented our experimental observations through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 30 publications
2
78
0
Order By: Relevance
“…Experimental observations showed that L lag is a complicated relationship between the flow conditions and geometry [1]. An adequate description is not available at the moment for L lag ; thus, in the present model, L lag is taken directly from experimental measurements and substituted into Eq.…”
Section: Lag Stagementioning
confidence: 99%
See 3 more Smart Citations
“…Experimental observations showed that L lag is a complicated relationship between the flow conditions and geometry [1]. An adequate description is not available at the moment for L lag ; thus, in the present model, L lag is taken directly from experimental measurements and substituted into Eq.…”
Section: Lag Stagementioning
confidence: 99%
“…The increase in size of the droplet during this stage is related to the time that the neck remains open and the flow rate of the dispersed phase. Only a portion of the continuous phase flow collapses the neck and this depends on this correlates with the fraction of the flow that is blocked by the interface [1].…”
Section: Neckingmentioning
confidence: 99%
See 2 more Smart Citations
“…One is to improve mixing in microchannels as in this paper [9]. Another important application is the generation of droplets and/or bubbles in two-phase systems [14][15][16].…”
Section: Introductionmentioning
confidence: 99%